Six Skills by Age Six : Launching Early Literacy at the Library - Foote, Anna; Debrick, Bradley (Santa Barbara, California : Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2016)
"This one-stop guide to nurturing six core early literacy skills at your library also offers practical tips for sharing these skills with parents, teachers, and other caregivers so they can institute them in playgroups, in school, or at home"--
From national to local : a brief history of 6 by 6 -- Establishing an early literacy program -- Helping children learn the six skills, and helping adults help children -- Have fun with books -- Talk, talk, talk -- Take time to rhyme, sing and play word games -- Notice print all around you -- Look for letters everywhere -- Tell stories about everything.
Includes bibliographical references and index.
Keywords: Children's libraries -- Activity programs -- United States; Libraries and preschool children; Libraries and caregivers; Language arts (Preschool); Reading readiness; Storytelling; Literacy programs -- Case studies -- Kansas; LANGUAGE ARTS & DISCIPLINES / Library & Information Science / General; EDUCATION / Teaching Methods & Materials / Reading & Phonics